Pharmacokinetic Studies of Trimoprostil in Rats (II): Blood level profile and tissue distribution during and after the consecutive oral administration of trimoprostil - TATEISHI, Mitsuru; TOMISAWA, Hiroki; ICHIMOTO, Noriko; FUKAZAWA, Hideo; ICHIHARA, Shigeyasu (Drug Metabolism and Pharmacokinetics, 1986)
3H-trimoprostil labeled at a C-11 methyl position was repeatedly given to rats of two sexes at a daily oral dose of 100 μg/kg for 14 days. The blood level profile and tissue accumulation of radioactivity were examined during and after the multiple administration. 1. Blood level profile The time course of 3H in the blood showed two peaks, one approximately 30 ?? 45 min and another 4 hr after respective dosing, then the blood concentration gradually decreased. The peak and minimum concentrations (24 hr level after each dosing) during the multiple administration were in the range of 1 ?? 2.1 times and 2.4 ?? 3.6 times higher than those observed after a single administration respectively. 2. Tissue accumulation The accumulation ratio (a ratio of concentration of 3H at 24 hr after the last dose of multiple administration, over 24 hr concentration after a single dosing) in each tissue was the same or lower in comparison to that (3.6 ?? 10) of the blood. Within 21 days after the cessation of multiple administration, 3H concentration in almost all the tissues other than the white fat pad decreased below the respective detection limits or 24 hr-levels after a single administration (100 μg/kg). The concentration of 3H in the fat pad on Day 21 after the last dose was as low as 20 ?? 24%of the level on day 1.